Pre-Clinical Pharmacological Profile of the Novel Glycoconjugate Org 36764 with both Factor Xa and Thrombin (IIa) Inhibitory Activities - Vogel, Gerard M. T.; van Amsterdam, Ronald G. M.; van Dinther, Theo G.; Tromp, Marijke; Meuleman, Dirk G. (Thrombosis and Haemostasis, 2000)
Org 36764, is an antithrombin III (AT) and thrombin binding carbohydrate, which accelerates the inactivation of both factor Xa and thrombin by AT. It displays in buffer an anti-Xa and anti-thrombin activity of 415 and 2 U/mg, respectively, compared to 172 and 114 U/mg, respectively, for unfractionated heparin (UFH). Org 36764 does not cross-react with HIT (heparin induced thrombocytopenia) antibodies and is not neutralised by PF4. In experimental models in rats, on a molar basis, Org 36764 was more active than the pentasaccharide SanOrg 34006 (= AT binding domain of Org 36764) in arterial thrombosis, but both were equally active in venous thrombosis. In arterial thrombosis following endothelial damage by ferric chloride, Org 36764 was more active than the LMW heparin enoxaparin and SanOrg 34006 and similar active to UFH. At AT saturating doses the bleeding enhancement was not more than 3.5 times the control value. Org 36764 was more active in suppressing in vivo thrombus formation on stents than UFH, SanOrg 34006 or a combination of ticlopidine and aspirin. The results indicate that the novel drug Org 36764 is a drug with antithrombotic potential against venous and arterial thrombosis.
Keywords: Inhibitor; factor Xa/IIa; synthetic; antithrombotic